Analytical Methods for Determination of Apremilast from Bulk, Dosage Form and Biological Fluids: A Critical Review. (7th May 2021) - Kulkarni, Pooja; Deshpande, Ashwini
Abstract: Apremilast is an anti-inflammatory agent. It has been a flourishing molecule in the field of dermatology. In the year 2014, Apremilast got its approval for treatment of psoriatic arthritis. Presently it is known to treat a number of other conditions, including atopic dermatitis and plaque psoriasis. Apremilast a phthalimide derivative, is non-hygroscopic in nature. It is practically insoluble in water. Apremilast acts by inhibiting the activity of phosphodiesterase 4 (PDE4), an intracellular enzyme. Analytical method plays a key role to understand the physio-chemical properties of a drug molecule. Because of poor solubility and low permeability, analytical method development and formulation becomes challenging. Till date, there are no standard test methods available to analyze Apremilast. So, a critical review of the analytical techniques of Apremilast was carried out. The literature search was done by screening the papers reporting analytical techniques of Apremilast from year 2014 to 2019. Methodologies particularly UV spectroscopy, HPTLC, HPLC, X-ray diffraction, NMR, LC-MS were collected and reviewed. Interminable efforts are made by the researchers to develop simple, accurate, robust and cost-effective methods of analysis. In pharmaceutical research, this information will aid in the development of new delivery systems. The review will prove beneficial and advantageous pre-formulation studies and will guide the formulation development.